Conditions for Oxygen-Packed Transportation of Penaeus Indicus seed - Geetha Rani V Mani (Department of Aquaculture, College of Fisheries, 1994)
The effect of four levels of packing density, (200PL/1, 300PL/1, 400PL/1 and 500PL/1), three levels of salinity (20ppt, 25ppt and 30ppt) and two levels of temperature (30_+ 1°C and 23 + 2°C) on the oxygen consumption rate of Penaeus indicus post-larvae (PL20) was investigated in a closed type respirometer. The dissolved oxygen in the test chamber decreased with the oxygen consumption of the animals. Oxygen consumption was found to vary with ambient oxygen levels at the different packing densities. Among the three salinities, and two temperatures, the lowest rate of oxygen consumption was recorded at 25ppt and 23 +_ 2°C. The effect of these factors on the duration and survival of transportation of the shrimp seed in specially designed hard plastic containers fitted with facilities for oxygen packing under uniform pressure (0.2 Kg/cm2) showed that oxygen packing in hypothermal conditions could help in increasing duration and survival. Salinity of 20-25ppt was found to give longer duration of survival. With increase in packing density, there was considerable reduction in the duration and survival of transportation of the seed.